Traumatic Brain Injury and Firearm Use and Risk of Progressive Supranuclear Palsy Among Veterans - Kelley, Kristen D.; Checkoway, Harvey; Hall, Deborah A.; Reich, Stephen G.; Cunningham, Chris; Litvan, Irene (Frontiers in Neurology, 2018)
Background: Progressive supranuclear palsy (PSP) is a tauopathy that has a multifactorial etiology. Numerous studies that have investigated lead exposure and traumatic brain injury as risk factors for other tauopathies, such as Alzheimer’s disease, but not for PSP. Objective: We sought to investigate the role of firearm usage, as a possible indicator of lead exposure, and traumatic brain injury as risk factors for PSP in a population of military veterans. Methods: We included participants from a larger case-control study who reported previous military service. Our sample included 67 PSP cases and 68 controls. Participants were administered a questionnaire to characterize firearm use in the military and occurrence of traumatic brain injury. Results: Cases were significantly less educated than controls. In unadjusted analyses, the proportion of PSP cases (80.6%) and controls (64.7%) who reported use of firearms as part of their military job was positively associated with PSP, odds ratio (OR) 2.2 (95% CI: 1-5.0). There were no significant case-control differences in mean service duration. There was only a weak association with history of traumatic brain injury, OR 1.6 (95% CI: 0.8-3.4). In multivariate models, firearm usage (OR 3.7, 95% CI: 1.5, 9.8) remained significantly associated with PSP. Conclusions: Our findings show a positive association between firearm usage and PSP and an inverse association between education and PSP. The former suggests a possible etiologic role of lead. Further studies are needed to confirm the potential etiologic effects of metals on PSP. The study was registered in clinicaltrials.gov. ClinicalTrials.gov Identifier: NCT00431301